Laparoscopic management of double moiety: A case report with review of literature - Agarwal, Nikhil Sanjiv Kumar; Shetty, Prakash Chandra; Joshi, Abhijit (Indian Journal of Case Reports, 2024)
Duplication of the ureter is one of the most common anomalies of the urinary tract. Ureterocele is a developmental anomaly with cystic dilation of the distal aspect of the ureter and is often associated with some urological anomaly, such as a duplicated system or stenotic ureteric orifice. Early detection of these anomalies during the antenatal period has dramatically increased due to advances in imaging technology. However, a few undiagnosed adults also exist. It may remain asymptomatic but may cause repeated urinary tract infections or calculi. This is a case report of a 47-year-old female who had bilateral duplex collecting systems with right ureterocele. The patient had a recurrent urinary tract infection. She underwent cystoscopic deroofing and a laparoscopic right total nephrectomy. Congenital anomalies of the urogenital system should be considered in patients with chronic or recurrent infections. Multimodal imaging techniques such as ultrasonography, computed tomography, or magnetic resonance imaging should be used to confirm the diagnosis, especially before surgical management. The rationale for reporting this case is to highlight this rare condition and the feasibility of its minimally invasive therapy.